Transcription Factors From Haematococcus pluvialis Involved in the Regulation of Astaxanthin Biosynthesis Under High Light-Sodium Acetate Stress - Wang, Chaogang; Wang, Kunpeng; Ning, Jingjing; Luo, Qiulan; Yang, Yi; Huang, Danqiong; Li, Hui (Frontiers in Bioengineering and Biotechnology, 2021)
Haematococcus pluvialis was paid close attention to its ability accumulating astaxanthin up to its 4% cellular dry weight under stress conditions such as high light, salt stress, nitrogen starvation. Previous research indicated that the regulation of astaxanthin synthesis might happen at transcription level. However, the transcription regulatory mechanism of astaxanthin synthesis still uncovered in H. pluvialis. Lack of studies on transcription factor further hindered from discovering this mechanism. Hence, the H. pluvialis under high light-sodium acetate stress for 1.5h was chosen to proceed transcriptome analysis. In total, 83,869 unigenes were obtained and anoteated in seven databases including NR, NT, KO, SwissProt, PFAM, KOG and GO. Moreover, 476 TFs belonged to 52 families were annotated by blasting with PlantTFDB. By comparing with conrtol group, we identified 4,367 DEGs composed of 2,050 up-regulated unigenes and 2,317 down-regulated unigenes. Most of them involved in metabolic process, catalytic activity, single-organism process, single-organism cellular process and single-organism metabolic process. In addition, 28 up-regulated TFs and 41 down-regulated TFs belonged to 27 TF families were found from transcriptome data, respectively. The transcription analysis showed TFs had different transcription modules responded to high light and sodium acetate stress. Interestingly, there were 6 TFs belonged to MYB, MYB_related, NF-YC, Nin-like and C3H fimilies might involve in the transcription regulation of 27 astaxanthin synthesis- related genes according to the regulatory network. Moreover, these TFs could affect astaxanthin synthesis by directly regulating CrtO, showing that CrtO was the hub gene in astaxanthin synthesis. The above of studies provided new insight into a global view of TFs and the correlationship between TFs and astaxanthin synthesis in H. pluvialis.